2009
DOI: 10.1117/12.806159
|View full text |Cite
|
Sign up to set email alerts
|

A novel efficient image compression system based on independent component analysis

Abstract: Next generation image compression system should be optimized the way human vision system (HVS) works. HVS has been evolved over millions of years for the images which exist in our environment. This idea is reinforced by the fact that sparse codes extracted from natural images resemble the primary visual cortex of HVS. We have introduced a novel technique in which basis functions trained by Independent Component Analysis (ICA) have been used to transform the image. ICA has been used to extract the independent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…(2) Calculating the inverse or pseudo inverse of bases matrix, we call the obtained matrix W . (3) Preprocessing the image which is to be compressed. First, divide the image into small square blocks.…”
Section: Ica For Natural Image Compressionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Calculating the inverse or pseudo inverse of bases matrix, we call the obtained matrix W . (3) Preprocessing the image which is to be compressed. First, divide the image into small square blocks.…”
Section: Ica For Natural Image Compressionmentioning
confidence: 99%
“…It has already been indicated that images of natural scenes are well modeled when the columns of A , which can be seen as a basis are wavelete-like filters, and the independent sources have heavy-tailed distributions [1] . That is to say, with high probability, only a small fraction of the elements of S have significant values; this sparse nature of S indicates the possibility of using overcomplete ICA to compression and denoising of natural images [1] .In [2,3] , the problem of using ICA for image compression is addressed. The authors of literature [2,3] have presented ICA based image compression system and got a promising performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In Refs. [2,3], the problem of using ICA for image compression is addressed. The authors of literature (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of literature (Refs. [2,3]) have presented ICA based image compression system and got a promising performance.…”
Section: Introductionmentioning
confidence: 99%